2009
DOI: 10.1590/s1516-14392009000400016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indentation load and time on knoop and vickers microhardness tests for enamel and dentin

Abstract: The aim of this study was to determine the effect of variations in indentation load and time on the Knoop and Vickers hardness numbers (KHN and VHN) for enamel and dentin. Twenty molar teeth were divided into twenty enamel and twenty dentin specimens. Each specimen was tested using a Knoop or Vickers microhardness tester at different loads and times. The difference in hardness between the groups was analyzed with two-way ANOVA followed by a Tukey test. The results revealed that a difference of indentation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 25 publications
7
79
0
2
Order By: Relevance
“…Our values for both mean BHN and KHN are in accordance with previously reported values of dentin microhardness [19, 20]. Moreover, similar to the previous study [7], BioDent RPI technique confirmed that the microhardness of dentin decreased apically toward deep dentin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our values for both mean BHN and KHN are in accordance with previously reported values of dentin microhardness [19, 20]. Moreover, similar to the previous study [7], BioDent RPI technique confirmed that the microhardness of dentin decreased apically toward deep dentin.…”
Section: Discussionsupporting
confidence: 92%
“…The typical indentation patterns obtained from Knoop and BioDent RPI at SD and DD are shown in Figure 2. The standard deviation associated with Knoop hardness numbers showed high variability similar to previous studies [19, 20]. Interestingly, variability was less pronounced in dentin microhardness results obtained by BioDent RPI (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several other factors could have also affected the measured hardness and wear volumes. Variations of enamel hardness values can be expected by factors such as specimen preparation, variation in chemical composition, tooth age, and location in the tooth [68]. E.g., it is known that enamel exhibits highly anisotropic orientation of enamel prism/rods and distribution of hydroxyapatite crystals [21].…”
Section: Relationship Between Hardness and Wearmentioning
confidence: 99%
“…It should be noted that in both studies the same prescribed values of load and pressing time were applied. The average values of Vickers microhardness given by Chuenarrom et al for both dentin and tooth enamel are much higher than the value of microhardness obtained for Lightdon Splint resin [25]. In fact, from the analysis of these data it can be concluded that the tested material has a lower hardness level than other available resins.…”
Section: Vickers Microhardness Testmentioning
confidence: 57%